Screening the occurrence of Grouper Iridovirus (Giv) in cage cultured Groupers in Sabah using Polymerase Chain Reaction (PCR) Technique - Julian Ransangan (Universiti Malaysia Sabah, 2007)
This investigation was conducted following mass mortalities of grouper larvae at the hatchery of the Borneo Marine Research Institute. Total genomic DNA from grouper larvae were extracted and subjected to polymerase chain reaction using specific primers targeting two genes, which are the major capsid protein and the ATPase genes of grouper iridovirus. However, none of the samples produced any visible band after the amplification of either gene. This however does not rule out the possibility of other viruses or bacteria causing the mass mortalities of grouper larvae in the hatchery. Therefore, it is recommended that investigation on the present of nervous necrosis virus (VNN) should also be conducted as these two viruses produce very similar disease manifestation when infecting grouper. Although, no iridovirus was detected in artificially produced grouper larvae at the Borneo Marine Research Institute, the precautionary measures should be monitored all the time as to prevent any viral contamination into the grouper broodstock already established in the hatchery.